Beyond the Schools of Psychology 2: A Digital Analysis of Psychological Review, 1904–1923. Issue 3 (9th June 2014) - Green, Christopher D.; Feinerer, Ingo; Burman, Jeremy T.
<x xml:space="preserve">Abstract</x> In order to better understand the broader trends and points of contention in early American psychology, it is conventional to organize the relevant material in terms of "schools" of psychology—structuralism, functionalism, etc. Although not without value, this scheme marginalizes many otherwise significant figures, and tends to exclude a large number of secondary, but interesting, individuals. In an effort to address these problems, we grouped all the articles that appeared in the second and third decades of Psychological Review into five‐year blocks, and then cluster analyzed each block by the articles' verbal similarity to each other. This resulted in a number of significant intellectual "genres" of psychology that are ignored by the usual "schools" taxonomy. It also made "visible" a number of figures who are typically downplayed or ignored in conventional histories of the discipline, and it provide us with an intellectual context in which to understand their contributions.